EDUCATIONAL FEATURES OF TEACHING ENGLISH IN THE TRAINING OF FUTURE TEACHERS - Jumaeva Sanobar Absaatovna, Umarova Gulzoda Bakhodir kizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The article examines the main tasks of methodological support for the educational process of training students - future teachers of English - to use game methods of control. Ways to improve curricula and programs within the framework of this area of training are proposed, and a teaching aid specially developed for the proposed special course is described.